AL-QURAN TADABBUR APPLICATION FOR SELF-LEARNING - Azman Ta’a; Nur Najibah Atiqah Abdul Aziz; Muhammad Shakirin Shaari @ Hj Ashari; Salina Ismail; Ahmad Suki Che Mohamed Arif (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
This research aims to create an al-Quran tadabbur application named Self-Tadabbur to provide a conducive learning environment for learners engaging by themselves to learn about the meaning of verses in al-Quran. This research’s significance lies in providing a new platform for learners to learn al-Quran by accessing features such as browsing and searching in different group elements, pairs, blocks, and subblocks of chapters. The tadabbur application is developed based on SALaM model, which caters specifically to exploring the al-Quran verses coherences and contributing to the development of Islamic software that facilitates the understanding of learners. The research adopted the Rapid Application Development (RAD) methodology for building the prototype and performing usability testing to evaluate the usability of the application. The evaluation was conducted on 30 randomly selected respondents from the Universiti Utara Malaysia (UUM) community. The results have shown that the tadabbur application was well-assisted by users to understand the meaning of al-Quran verses.